2020
DOI: 10.1016/j.tox.2020.152405
|View full text |Cite
|
Sign up to set email alerts
|

The Fusarium mycotoxin, 2-Amino-14,16-dimethyloctadecan-3-ol (AOD) induces vacuolization in HepG2 cells

Abstract: The Fusarium mycotoxin, 2-Amino-14,16-dimethyloctadecan-3-ol (AOD) induces vacuolization in HepG2 cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Ingestion of fumonisin-contaminated feed results in various animal diseases . High incidences of human esophageal cancer and liver cancer have also been associated with the consumption of fumonisin-contaminated corn. Both 2-AOD-3-ol and Fumonisin B1 lack 1-hydroxyl on the sphingoid base that can be subclassified as the atypical 1-deoxysphinganine analogue according to their structural features . Uhlig et al reported that the mechanisms leading to the cytotoxicity of 2-AOD-3-ol may not be like Fumonisin B1 inhibition of biosynthesis of typical ceramides because it has no apparent effects on the sphinganine/sphingosine ratio .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ingestion of fumonisin-contaminated feed results in various animal diseases . High incidences of human esophageal cancer and liver cancer have also been associated with the consumption of fumonisin-contaminated corn. Both 2-AOD-3-ol and Fumonisin B1 lack 1-hydroxyl on the sphingoid base that can be subclassified as the atypical 1-deoxysphinganine analogue according to their structural features . Uhlig et al reported that the mechanisms leading to the cytotoxicity of 2-AOD-3-ol may not be like Fumonisin B1 inhibition of biosynthesis of typical ceramides because it has no apparent effects on the sphinganine/sphingosine ratio .…”
Section: Discussionmentioning
confidence: 99%
“…19−21 Both 2-AOD-3-ol and Fumonisin B1 lack 1hydroxyl on the sphingoid base that can be subclassified as the atypical 1-deoxysphinganine analogue according to their structural features. 9 Uhlig et al reported that the mechanisms leading to the cytotoxicity of 2-AOD-3-ol may not be like Fumonisin B1 inhibition of biosynthesis of typical ceramides because it has no apparent effects on the sphinganine/ sphingosine ratio. 22 However, our novel discovery on acyl derivatives of 2-AOD-3-ol provides new insight into the understanding of the hepatic and neurological toxicities of mycotoxins.…”
Section: Journal Ofmentioning
confidence: 99%
See 2 more Smart Citations